Hubungan Learning Approach Dengan Nilai Objective Structured Clinical Examination (OSCE) Mahasiswa Fakultas Kedokteran Universitas Riau Tahun Kedua - Zulfi Mustika Rantari; Zulharman Zulharman; Enikarmila Asni (Fakultas Kedokteran Universitas Riau, 2018)
The learning approach is the way to achieve their learning objectives. Learning approach can influence the OSCE value. This study aimed to analyze the relationship between learning approach and OSCE value. This study was analytic descriptive with cross-sectional design. The subjects were all the medical student University of Riau in the second year. Study Process Questionnaire (SPQ) which have been translated to Indonesia language was used in this study. OSCE value before remedial data were analyzed using Kruskal-Wallis. The majority of students (93.1%) using the achieving approach and there were no relationship between learning approach and OSCE value. lue.